2007
DOI: 10.1038/sj.onc.1210872
|View full text |Cite
|
Sign up to set email alerts
|

Activation and regulation of ATM kinase activity in response to DNA double-strand breaks

Abstract: The ataxia-telangiectasia-mutated (ATM) protein kinase is rapidly and specifically activated in response to DNA double-strand breaks in eukaryotic cells. In this review, we summarize recent insights into the mechanism of ATM activation, focusing on the role of the Mre11/Rad50/Nbs1 (MRN) complex in this process. We also compare observations of the ATM activation process in different biological systems and highlight potential candidates for cellular factors that may participate in regulating ATM activity in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
385
1
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(405 citation statements)
references
References 86 publications
13
385
1
6
Order By: Relevance
“…The complex can tether linear duplex molecules [39], and it is able to bridge broken DNA ends or sister chromatids [40]. MRN function is complex as it also acts downstream of ATM to facilitate the phosphorylation of numerous substrates including Smc1 and Chk2 [3]. On the basis of our results, we hypothesize that action of tungstate on the ATM kinase is exerted upstream, at the DNA damage site, or downstream, thus affecting the negative regulation of the kinase.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The complex can tether linear duplex molecules [39], and it is able to bridge broken DNA ends or sister chromatids [40]. MRN function is complex as it also acts downstream of ATM to facilitate the phosphorylation of numerous substrates including Smc1 and Chk2 [3]. On the basis of our results, we hypothesize that action of tungstate on the ATM kinase is exerted upstream, at the DNA damage site, or downstream, thus affecting the negative regulation of the kinase.…”
Section: Discussionmentioning
confidence: 78%
“…Analysis of ATM activation and substrates such as SMC1 showed that the ATM signalling cascade was activated in these treatments and was affected by tungstate [3]. The MRN complex has diverse functions in DNA damage recognition [34], cell cycle checkpoint activation [35], non-homologous end joining [36] and telomere maintenance [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that ATR is activated due to the presence of single strand DNA (ssDNA) whereas ATM is triggered in response to DNA double strand breaks (DSBs). In response to DNA double strand breaks, ATM is recruited to the double strand ends by the three proteins Mre11, RAD50 and NBS1-formed complex (MRN complex) (Lee and Paull, 2007) and phosphorylates the histone H2AX on Ser139 (Huang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…MRN detects and localises rapidly to DSBs after damage and secures and shields the frayed DNA ends (Williams and Tainer 2005) whilst activating checkpoint signalling via ATM (Lee and Paull 2007;Williams and Tainer 2005). Two Mre11 and two Rad50 molecules form a heterotetramer that interacts with Nbs1 (Xrs2 in yeast) and can bind both ends of a DSB, although Mre11 can itself form homomultimers (reviewed in ).…”
Section: Mre11mentioning
confidence: 99%